Making sense of ambiguity: evaluation in internal reliability and face validity of the SF 36 questionnaire in women presenting with menorrhagia. Issue 1 (March 1996) - Jenkinson, C; Peto, V; Coulter, A
Abstract : OBJECTIVE–To determine the face validity and internal reliability of the short form 36 (SF 36) health survey questionnaire in women presenting with menorrhagia. DESIGN–Postal survey of women recruited by their general practitioners followed by interviews of a selected subsample. PATIENTS–348 women who had consulted their general practitioner with excessive menstrual bleeding and completed questionnaires after treatment. 49 women selected from this group were interviewed in depth about their health status, and requested to complete the SF 36 questionnaire. MAIN MEASURES–Subjective accounts of functioning and wellbeing as measured by the eight scales of the SF 36 questionnaire. RESULTS–Data from the postal survey indicated that the ¿general health perceptions¿ and ¿mental health¿ scales of the SF 36 questionnaire had lower internal reliability coefficients than documented elsewhere. In the follow up interviews several questions on the SF 36 questionnaire were commented on as inappropriate or difficult to answer for patients with heavy menstrual bleeding. CONCLUSIONS–Some questions on the SF 36 questionnaire were difficult to answer for this group of patients. Such problems can adversely effect the validity of the measure. It is suggested that comments of patients upon measures such as the SF 36 questionnaire could both determine the appropriateness of such measures for given studies and influence questionnaire design.